A facile approach to incorporate silver nanoparticles into solvent-free synthesized PEG-based hydrogels for antibacterial and catalytical applications. (September 2021) - Kazeminava, Fahimeh; Arsalani, Nasser; Ahmadi, Raman; Kafil, Hossein Samadi; Geckeler, Kurt E.
Abstract: This work aimed to immobilize silver nanoparticles with catalytic and antibacterial activity (AgNPs) inside of the PEG-based hydrogel through a facile and green design. First, the hybrid hydrogels were prepared under solvent-free conditions based on dianhydride ethylenediamine tetraacetic acid, poly (ethylene glycol) of different molar mass, glycerol, and octa-aminopropyl polyhedral oligomeric silsesquioxane hydrochloride salt as organic and inorganic cross-linker agent. The well-dispersed AgNPs were fabricated in-situ in the polymeric matrix of the hybrid hydrogel through the reduction of Ag + by NaBH4 . The resulting hybrid nanocomposite hydrogels were characterized by various techniques, such as FT-IR spectroscopy, SEM, TEM, EDX, XRD, BET, and TGA. The swelling behavior, the antibacterial activity against the bacteria S. aureus (Gram-positive), and E. coli (Gram-negative), as well as the catalytic efficiency for the reduction reaction of 4-nitrophenol to 4-aminophenol of the nanocomposite hydrogels prepared, were examined. The facile and mass production synthetic method of the nanocomposite hydrogels, excellent dispersion of the AgNPs inside the hydrogel matrix, excellent catalytic recyclability, and antibacterial activity are some of the advantages of this system. The maximum inhibition zone was found to be 17.4 and 15.9 mm against the gram-positive species S. aureus and the gram-negative E. coli, respectively. Besides, the maximum catalytic activity was achieved in a short time period of 30 s. Highlights: The hybrid hydrogels were prepared under solvent-free conditions. The well-dispersed AgNPs were fabricated in-situ in the polymeric matrix of the hybrid hydrogel. The maximum catalytic activity was achieved in the short time period of 30 s. The catalytic recyclability and antibacterial activity were excellent. All experimental hydrogels had pronounced antibacterial and catalytic activities.